Os Impactos da covid-19 na educação: os desafios impostos pelas mídias digitais aos docentes do componente curricular matemática de uma escola de ensino médio de Goiânia – GO - TRAVASSOS, Adriana Moreira (2023)
This work is entitled as: The Impacts of Covid-19 on education: The challenges imposed by digital media to teachers of the Mathematics curriculum component of a high school in Goiânia - GO. The present investigation was based on the need to know the professional profile of the investigated teachers, in order to allow possible debates on their adaptation to remote teaching. In this sense, the research aims to understand how teachers of the high school mathematics curriculum component of a public school in Goiânia (GO) dealt with teaching through digital media and how they adapted their methodologies during the pandemic. The investigation was carried out with three teachers of the mathematics curriculum component of a high school in the city of Goiânia-GO. To achieve this objective, a reference research was initially carried out showing a brief history of the impacts of Covid-19 on the Brazilian educational system and, in particular, in Goiânia; document analysis, appreciating documents published by the country's federal government, as well as regional and local guidelines for remote teaching in this period. Following the completion of the project, a questionnaire was organized with semi-structured questions applied to teachers. Finally, the analysis of the collected data and presentation of the most relevant ones. The results obtained in the research show that the pedagogical practices of the researched school are being guided by the CNE guidelines, being developed with the help of the WhatsApp application, NetEscola Portal and broadcast on TV and radio. The narratives about the physical and mental fatigue experienced by the teachers cannot be ignored. Teachers are exposed to various situations and pressures from institutions, which results in illness, especially related to mental health. As a suggestion aimed at caring for the mental health of these professionals, we point to the creation of virtual spaces interconnected with multidisciplinary teams.